A qualitative study of safe abortion and post-abortion family planning service experiences of women attending private facilities in Kenya - Suzanne Penfold; Susy Wendot; Inviolata Nafula; Katharine Footman (BMC, 2018)
Abstract Background To inform improvements in safe abortion and post-abortion family planning (PAFP) services, this study aimed to explore the pathways, decision-making, experiences and preferences of women receiving safe abortion and post-abortion family planning (PAFP) at private clinics in western Kenya. Methods We conducted semi-structured interviews with 22 women who had recently used a safe abortion service from a private clinic. Interviews explored abortion-seeking behaviour and decision-making, abortion experience, use and knowledge of contraception, experience of PAFP counselling, and perceived facilitators of and challenges to family planning use. Results Respondents discovered their pregnancies due to physical symptoms, which were confirmed using pregnancy testing kits, often purchased from pharmacies. Respondents usually discussed their abortion decision with their partner, and, sometimes, carefully-selected friends or family members. Some reported being referred to private clinics for abortion services directly from other providers. Others had more complex pathways, first seeking care from unsafe providers, trying to self-induce abortion, being turned away from alternative safe facilities that were closed or too busy, or taking time to gather financial resources to pay for care. Participants wanted to use abortion services at facilities reputed for being accessible, clean, medically safe, and offering quick, respectful, private and courteous services. Awareness of reputable clinics was gained through personal experience, and recommendations from contacts and other health providers. Most participants had previously used contraception, with some reports of incorrect use and many reports of side effects. PAFP counselling was valued by clients, but some accounts suggested the counselling lacked comprehensive information. Many women chose contraception immediately following PAFP counselling; but others wanted to delay decision-making about contraception until the abortion was complete. Conclusion Women's pathways to safe abortion care can be complex, including use of multiple abortion methods, delays due to financial barriers, and challenges accessing safe providers. Improvements in community knowledge of safe abortion care and accessibility of services are needed to reduce recourse to unsafe abortion. PAFP counselling is valued by clients but quality of counselling can be improved by exploring women's contraceptive histories, including information on more contraceptive methods, and inclusion of support for women who want to delay family planning uptake until their abortion is complete.